Design and Development of a Data Logger Based on IEEE 802.15.4/ZigBee and GSM: Design and Development of a Data Logger Based on IEEE 802.15.4/ZigBee and GSM - Asif, Muhammad; Ali, Muhammad; Ahmad, Naveed; Haq, Sana Ul; Jan, Tariqullah; Arshad, Muhammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The Data Logger (DL) is a special device which is designed to accomplish a common task that is to collect data in a targeted area. Some of the DLs have onboard integrated sensors while some collect data using the wireless sensor nodes WSNs. According to the literature some of the proposed DLs are expensive and slow in operation while some do not fulfill all the application requirements i.e. long and short range data logging. Thus a cost efficient, fast and a wireless DLs are the need of a day. In this paper a customized wireless DL is designed, which is cost efficient, fast and can perform in a wide and short range. The designed data logger is based on IEEE 802.15.4 and GSM Technology and use a 32bit microcontroller as a central processing unit. The designed DL is beneficial for the researchers and application developers in data logging and monitoring of environment, weather and road traffic etc.